Rapidly varying boundaries in equations with nonlinear boundary conditions. The case of a Lipschitz deformation - Arrieta, Jose M.; Bruschi, Simone M. [UNESP] (World Scientific Publ Co Pte Ltd, 2007)
We analyze the behavior of solutions of nonlinear elliptic equations with nonlinear boundary conditions of type partial derivative u/partial derivative n + g( x, u) = 0 when the boundary of the domain varies very rapidly. We show that the limit boundary condition is given by partial derivative u/partial derivative n+gamma(x) g(x, u) = 0, where gamma(x) is a factor related to the oscillations of the boundary at point x. For the case where we have a Lipschitz deformation of the boundary,. is a bounded function and we show the convergence of the solutions in H-1 and C-alpha norms and the convergence of the eigenvalues and eigenfunctions of the linearization around the solutions. If, moreover, a solution of the limit problem is hyperbolic, then we show that the perturbed equation has one and only one solution nearby.
Keywords: varying boundary; oscillations; nonlinear boundary conditions; elliptic equations